Impact of Healthcare Associated Infections on Survival and Treatment Outcomes Among End Stage Renal Disease Patients on Renal Replacement Therapy - Abbasi, Saad Hanif; Aftab, Raja Ahsan; Lai, Pauline Siew Mei; Lim, Soo Kun; Zainol Abidin, Ruwaida Nur (Frontiers in Pharmacology, 2021)
Background Due to frequent hospitalizations, complex dialysis procedures and immune compromising effects of end stage renal disease (ESRD), patients on dialysis are more prone to healthcare associated infections (HCAIs). Objective To study the impact of HCAIs on survival and treatment outcomes among ESRD patients on renal replacement therapy (RRT). Methodology A multicenter, retrospective study was conducted from June to December 2019 at two public hospitals of Malaysia. ESRD patients with minimum of 6 months on RRT were included, while pregnant patients and patients <18 years were excluded. Multinomial logistic regression was performed to identify risk factors associated with unsuccessful treatment outcomes. Kaplan Meier analysis was performed to study the survival. Results A total of 670 records were examined, of which 400 patients were included as per the inclusion criteria. The mean survival time of patients without HCAIs [22.7(95%CI:22.1–23.2)] was higher than the patients with HCAIs [19.9(95%CI:18.8–20.9)]. Poor survival was seen in patients with >2 comorbidities, >60 years of age, low hemoglobin concentration and high C-reactive protein levels. The most frequent treatment outcome was cured [113(64.9%)], followed by death [37(21.3%)] and treatment failure [17(9.8%)]. Advancing age, and low hemoglobin concentration were independent risk factors associated with death, while recurrent HCAIs, use of central venous catheters, and low serum sodium levels were risk factors for treatment failure. Conclusion The high burden of HCAIs is a profound challenge faced by patients on RRT, which not only effect the treatment outcomes but also contribute substantially to the poor survival among these patients.